Waste thermal energy harvesting from a convection-driven Rijke–Zhao thermo-acoustic-piezo system - Zhao, Dan (2013)
In this work, a convection-driven Rijke–Zhao thermo-acoustic-piezo system is designed and experimentally tested to demonstrate its potential for harvesting thermal energy. For this, a nonlinear theoretical model is developed to simulate the energy conversion process, i.e. heat-to-sound-to-electricity in the present system. Unlike the conventional conduction-driven thermoacoustic converters, our present system involves no heat exchangers and stacks. As a heat source is placed in a Rijke–Zhao tube with two bifurcating daughter branches, self-sustained thermoacoustic oscillations are generated. The resulting acoustic fields in the bifurcating branches are dramatically different. One branch is associated with ‘hot’ oscillations. However the other is with ‘cold’ oscillations at ambient temperature, which enable a piezoelectric generator being implemented to the end of the branch. In order to measure the acoustic fields in the bifurcating branches, two arrays of thermocouples and microphones are used. The maximum sound pressure level is around 139 dB. The output electric power and acoustical energy conversion efficiency are measured and compared with that from a similar but a conduction-driven thermo-acoustic-piezo system. It is found that 60% more power is generated. And the energy conversion efficiency is increased by 105%. These experimental results confirm that the developed Rijke–Zhao thermo-acoustic-piezo system is an invaluable tool in designing a simple, low-cost, energy-efficient thermoacoustic system.